2023
DOI: 10.1111/1471-0528.17698
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2—Placental effects and association with stillbirth

Abi Merriel,
Brendan Fitzgerald,
Keelin O’Donoghue

Abstract: SARS‐CoV‐2 has had a significant impact on pregnancy outcomes due to the effects of the virus and the altered healthcare environment. Stillbirth has been relatively hidden during the COVID‐19 pandemic, but a clear link between SARS‐CoV‐2 and poor fetal outcome emerged in the Alpha and Delta waves. A small minority of women/birthing people who contracted COVID‐19 developed SARS‐CoV‐2 placentitis. In many reported cases this was linked to intrauterine fetal death, although there are cases of delivery just before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 129 publications
0
1
0
Order By: Relevance
“…Studies have reported that SARS-CoV-2-associated fetal demise is not linked to the severity of the disease in pregnant mothers [ 6 8 ] and occurs between 21 and 39 weeks of gestation [ 7 , 9 ], consistent with our case. Reports suggest that unvaccinated women with different clinical manifestations may develop placental pathological features with rapid deleterious fetal outcomes occurring between 3 and 15 days after receiving a COVID-19 diagnosis [ 10 12 ]. In our patient, maternal SARS-CoV-2 detection was followed by the diagnosis of fetal demise, due to asymptomatic status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that SARS-CoV-2-associated fetal demise is not linked to the severity of the disease in pregnant mothers [ 6 8 ] and occurs between 21 and 39 weeks of gestation [ 7 , 9 ], consistent with our case. Reports suggest that unvaccinated women with different clinical manifestations may develop placental pathological features with rapid deleterious fetal outcomes occurring between 3 and 15 days after receiving a COVID-19 diagnosis [ 10 12 ]. In our patient, maternal SARS-CoV-2 detection was followed by the diagnosis of fetal demise, due to asymptomatic status.…”
Section: Discussionmentioning
confidence: 99%